Formulation and In-Vitro Evaluation of Polymer-Based Extended-Release Pellet Tablets of Diltiazem : Pharmaceutical sciences- Pharmaceutics - Arora, Sahil; Rathore, Charul (International Journal of Life Science and Pharma Research, 2023)
An important development in cardiovascular health is the creation of a blood pressure-lowering extended-releaseformulation. With this novel method, antihypertensive medications are released gradually and continuously, ensuring ideal bloodpressure levels all day long. Reducing the frequency of medicine administration improves ease for patients and adherence, whichhas a positive impact on long-term results. The regulated distribution technique used in this formulation not only increasesefficacy but also reduces the possibility of adverse effects, improving patient comfort and overall quality of life. The extendedrelease formulation has the potential to revolutionise the treatment of hypertension by providing people with high bloodpressure with a more effective and secure option. The main objective is to formulate an Extended-release formulation to lowerBP, which improves patient compliance, reduces the dose frequency, and minimizes the fluctuations seen by immediate-releasetablets, which require multiple dose administration throughout the day. Diltiazem (DTZ) of Extended-release pellet tablets wasformed by using Wurster Coater Granulator to load and coat the pellets with the drug using different polymers, and the Preformulation study was carried out. To check the compatibility of DTZ with other polymers, a DSC and FTIR study was carriedout to make pure and more stable formulations. The pellet tablet products' dissolution profile and physicochemical parametersare compared. DTZ of extended-release pellets in-vitro dissolution study was done using pH 4.5/ 6.8 phosphate buffer usingUSP-2 type method for 2, 3, 4, 6, 8, 12, 18, 24, and 30 hrs. For the drug release profile, significant differences were checked fordifferent formulations. The highest release rate of drug retarding was shown by those with higher polymer content. DSC andFTIR carried out the characterization of DTZ to check the compatibility of the drug with polymers or not. The stability studywas carried out for different months to develop a stable formulation. It was concluded that DTZ of Extended-release pellettablets helps treat hypertension by releasing the drug throughout the day for 30 hours. It helps in lowering BP and preventsvarious cardiovascular complications.